Van Gogh's sunflowers illuminated art meets science - Hendriks, Ella 1960-; Vellekoop, Marije 1969- (Amsterdam University Press, 2019)
This book is entirely devoted to the research performed over the years into Van Gogh's Sunflowers, an icon of Western European art. Vincent van Gogh's 'Sunflowers' are seen by many as icons of Western European art. Two of these masterpieces - the first version painted in August 1888 (The National Gallery, London) and the painting made after it in January 1889 (Van Gogh Museum, Amsterdam) - have been the subject of a detailed comparison by an interdisciplinary team of experts. The pictures were examined in unprecedented depth using a broad array of techniques, including state-of-the-art, non-invasive imaging analytical methods, to look closely at and under the paint surface. Not only the making, but also the subsequent history of the works was reconstructed, including later campaigns of restoration. The study's conclusions are set out in this book, along with the fascinating genesis of the paintings and the sunflower's special significance to Van Gogh. More than 30 authors, all specialists in the field of conservation, conservation science and art history, have contributed to the research and publication presenting the outcomes of this unique project
Keywords: Gogh, Vincent van -- 1853-1890 -- Sonnenblumen; Restaurierung; Naturwissenschaften; Gogh, Vincent van / 1853-1890 / Themes, motives; Sunflowers in art; Aufsatzsammlung